2009
DOI: 10.5539/ibr.v2n4p109
|View full text |Cite
|
Sign up to set email alerts
|

Communication Skill of the Business Executives: An Empirical Study on Some Local Private Business Concerns in Bangladesh

Abstract: The study which is mainly based on primary data attempts to focus on the facts relating to the communication skill of the different levels of business executives of local private business concerns in Bangladesh and their level of awareness regarding the importance of communication skill in their professional career. The study reveals that majority of the executives have positive opinions regarding the importance of communication course designed for executives. Most of the respondents have completed communicati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
2
2

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…In academia and professional training context as well, the non-verbal communication skills and other facilitators for effective communication are visibly underrepresented. Akhter, Khan and Hassan (2009) found that the executives have positive attitudes towards the importance of communication course intended for executives. Most of the executive respondents completed communication course and they were dissatisfied with it.…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…In academia and professional training context as well, the non-verbal communication skills and other facilitators for effective communication are visibly underrepresented. Akhter, Khan and Hassan (2009) found that the executives have positive attitudes towards the importance of communication course intended for executives. Most of the executive respondents completed communication course and they were dissatisfied with it.…”
Section: Introductionmentioning
confidence: 93%
“…Communication skill is one of the most important soft skills for the business executives according to the extant human resource management (HRM) literature (Akhter, Khan, & Hassan, 2009). However, the ways to design an effective communication training or development program for the business executives have rarely been explored.…”
Section: Introductionmentioning
confidence: 99%
“…Our findings are consistent with previous research. Akhter et al (2009) found that most business organizations in Bangladesh had no arrangements for training program on communication skills and negotiation for their employees. However, the majority of business executives felt that they needed training on communication skills and negotiations for successful business deals with foreign partners.…”
Section: Problems In Negotiationmentioning
confidence: 99%